Development of inherently safer design approaches to prevent or minimize toxic release accidents at the preliminary design stage - ZAINI, DZULKARNAIN (2012)
Inherent safety has been accepted as one of the best techniques to prevent or minimize major accidents in process plants. The best implementation is during the preliminary design stage. Even though it has been acknowledged as an attractive benefit in terms of safety and cost performance, the actual implementation of inherent safety in the process design stage is not widely implemented in the industries. The unavailability of a user friendly tool due to the lack of integration between process design simulators with inherent safety quantification is one of the difficulties for designing an inherently safer design process. Current research and development are focusing specifically for the case of explosion and fire only. None of these techniques were developed to prevent or minimize the major accidents due to toxic release accidents. Therefore, this work develops and proposes a new technique that can quantify the level of inherent safety for process routes, streams and evaluate the inherent risk for toxic release accidents. The combination of the above techniques provides the best solution which is known as 3-Tier Inherent Safety Quantification (3- TISQ). The 3-TISQ allows for risk reduction through the implementation of inherent safety principles during the preliminary design stage. A new concept of inherent risk based on a 2-region risk matrix that is suitable during the preliminary design stage is developed and used in the 3-TISQ.